Improving the Understanding of the Redox Properties of Fluoranil Derivatives for Cathodes in Sodium‐Ion Batteries. Issue 22 (17th October 2019) - Jung, Ku Hyun; Jeong, Gyeong Seok; Joo, Ji Bong; Kim, Ki Chul
Abstract: Despite the potential of organic cathodes in sodium‐ion batteries, their redox properties still need to be explored. In this study, a density functional theory modeling approach is employed to comprehensively investigate the redox properties and theoretical performance parameters for a selected set of fluoranil derivatives as cathode materials. The redox properties are further correlated with various characteristics including structural variations, electronic properties, and solvation. Three primary conclusions are drawn. First, the incorporation of bulky trifluoromethyl functional group(s) into fluoranil increases its redox potential but significantly decreases its gravimetric charge capacity. This suggests that the trifluoromethyl functional group(s) would be detrimental to the design of high‐performance batteries. Second, fluoranil exhibits significant enhancements in terms of redox properties and theoretical performance compared with its hydrogenated form, benzoquinone, suggesting a desired strategy for designing high‐performance batteries. Third, the redox properties of fluoranil derivatives would strongly rely not only on structural variations (e.g., bulkiness) and electronic properties (e.g., functionality) but also on solvation energy. It is further verified that cathodic deactivation could be completed by solvation energy. The new understanding will provide us with guidelines for an efficient design of promising organic cathode materials. Abstract : United Na‐ions : Despite the potential of organic cathodes in sodium‐ion batteries, their redox properties still need to be explored. Density functional theory modeling is employed to comprehensively investigate the redox properties and theoretical performance parameters for a selected set of fluoranil derivatives as cathode materials. The redox properties are further correlated with various characteristics including structural variations, electronic properties, and solvation.